Investigating the Prevalence of Head and Upper Extremity Deformities in Students with Special Need - Mozhgan Farahbod; Mina Ahmadi-Kahjough; Mahsa Sattari (University of Social Welfare and Rehabilitation Sciences, 2016)
Objectives: Musculoskeletal disorders are the most common childhood problems. The aim of the present study was to investigate the prevalence of head and upper extremity deformities in children with special needs. Materials & Methods: The present research is a descriptive cross-sectional study with stratified sampling method. Ten percent of students with mental retardation, hearing impairment and sight impairment in the academic year of 2012-13 were selected for this study. There were 1194 persons in Tehran, 1526 people in the cities of the Tehran Province and 559 students in Alborz Province. In total, 3279 people participated in the study. Demographic questionnaire and a plummet were used for data collection. Data was reported using descriptive statistics. Results: The results of the study revealed that "dropped shoulder" in girls of Alborz province with visual impairment with 100% had the highest rate and this abnormality in boys with visual impairment in the Tehran had the least prevalence. In the deformities of the head, lateral head bending with 76.6% in girls with visual impairment in Tehran, and forward head posture with 83.3% in boys with visual impairment in cities of Tehran had the highest incidence in comparison with others. Conclusion: The prevalence of upper extremity deformities is high in students with special needs including mental retardation, hearing impairment and sight impairment. It is necessary to diagnose these deformities in time.